Analisis Guessability Score dan Pemahaman Piktogram Kefarmasian pada Pasien Tuberkulosis - Ema Rachmawati; Dhea Nanda Aliefia; Fransiska Maria Christianty (Universitas Islam Indonesia, 2023)
Background: Pharmaceutical pictograms can be used to help tuberculosis patients understand treatment information, especially those with low reading skills.Objective: This study aimed to analyze the guessability score and the level of understanding of pharmaceutical pictograms related to the use of TB drugs.Method: This was an observational study with a cross-sectional design. The sample used was 96 TB patients who were actively undergoing treatment. The guessability score and level of understanding were analyzed descriptively, while the relationship between socio-demographic characteristics and the level of understanding of pharmaceutical pictograms was analyzed using the Chi-square test.Results: The results showed that the guessability score of 23 pictograms tested on respondents varied greatly, with a score range of 29.2%–99%. Meanwhile, the level of respondents' understanding of pharmaceutical pictograms related to TB treatment was in the